Molecular characterization and virulence gene profiling of methicillin-resistant Staphylococcus aureus associated with bloodstream infections in southern China - Zhao, Rui; Wang, Xing; Wang, Xinhui; Du, Bingyu; Xu, Kexin; Zhang, Faming; Jiang, Changhong; Zhao, Yanfeng; Zhu, Yefei (Frontiers in Microbiology, 2022)
Methicillin-resistant Staphylococcus aureus (MRSA) causes an enormous illness burden, including skin and soft tissue infections (SSTIs), pneumonia, bloodstream infections (BSI), and sepsis. BSI are associated with significant patient morbidity and mortality worldwide. However, limited information is available on MRSA-related BSI in China. This study aimed to investigate the molecular characterization of 77 MRSA isolates recovered from hospitalized patients with BSI between 2012 and 2020 at three first-class tertiary hospitals in southern China based on multilocus sequence typing (MLST), spa typing, and staphylococcal cassette chromosome mec (SCCmec) typing. Overall, 13 clonal complexes (CCs) were identified, with CC59 and CC5 being the largest clusters, indicating high genetic diversity among BSI-causing MRSA isolates. ST59 was the most prevalent MLST type (22.1%). ST5/ST764-MRSA SCCmec II was the predominant adult MRSA clone, whereas ST59-MRSA SCCmec IV was the most common pediatric MRSA clone. ST5-t2460, ST764-t1084, and ST59-t437 were the most common types of adult MRSA isolates, whereas ST59-t437 and ST59-t172 were the predominant types of children’s MRSA isolates. ST59-SCCmec IV/V represented the most common clone among community acquired-MRSA isolates. ST5/ST764-SCCmec Ⅱ was the most common type of hospital-associated MRSA isolate. The most prevalent toxin-encoding genes detected were hla, hld, icaA, and clfA (96.1%–100%). Forty-three (100%, 43/43) isolates harbored more than 18 of the tested virulence genes in adults and 8 virulence genes (23.5%, 8/34) in children. Virulence gene analysis revealed diversity among different clones: the positivity rates for the Panton-Valentine leukocidin (PVL) gene were 55.8% and 35.3% in adult and pediatric MRSA isolates, respectively; the genes seb–sei were present in all adult strains; seb–seg–sei–seo were present in all ST5, ST59, ST15, ST45, and ST22 adult strains; and seg–sei–sem–sen–seo were present in different clones, including ST15, ST45, and ST22 adult MRSA isolates and ST25, ST30, ST546, and ST72 children’s MRSA isolates. Adult MRSA isolates had significantly higher antibiotic resistance rates and virulence gene prevalence than pediatric MRSA isolates. For eight years, this study provided epidemiological data on the molecular characteristics and virulence genes in different groups of MRSA BSI in China. Our findings may provide critical information for a better understanding of MRSA BSI.